Tinjauan Yuridis Tindak Pidana Peredaran Narkotika Jenis Shabu Studi Putusan “731/Pid.Sus/2022/PN.Mks” - Andi Rahma; Andi Zulkarnain; Ernalia Rahayu (Pledoi Law Jurnal, 2023)
ABSTRACT: The purpose of this research is to determine the application of criminal law regarding the distribution of the drug known as shabu, in order to understand the judge's law in imposing criminal sanctions on the perpetrator of the distribution of the drug known as shabu in the case "Number 731/Pid.Sus/2022/PN.Mks". The research method used is normative law, and the data analysis used in this research is qualitative data analysis. The research results show that (1) The application of criminal law regarding the crime of drug trafficking committed by the defendant Siskawanti Alias Siska Binti M. Said in Decision Number 731/Pid.Sus/2022/PN.Mks has been proven legally to fulfill the elements contained in Article 114 paragraph 2 of the Indonesian Law Number 35 of 2009 concerning Narcotics. (2) The criminal sanctions should be in accordance with the demands of the Public Prosecutor, because the criminal responsibility of the drug dealer perpetrator based on the facts and testimonies of the two witnesses is clearly committed by the defendant Siskawanti Alias Siska Binti M. Said, who is a drug courier where the defendant was ordered by Ari Sincan with a salary of 5 (five) million rupiahs to take shabu and deliver it to the buyer with a weight of 46.8711 grams and a final weight of 45.3450 grams. The defendant's actions are very detrimental to herself and others. ABSTRAK: Tujuan Penelitian ini ialah untuk mengetahui penerapan hukumpidana materil pengedar narkotika jenis shabu untuk mengetahui hukumhakim dalam menjatuhkan sanksi pidana terhadap pelaku pengedar narkotikajenis shabu yang dilakukan pada perkara ”Nomor 731/Pid.Sus/2022/PN.Mks. Metode penelitian ini adalah hukum normatif, analisis data yang digunakan dalam penelitian ini adalah analisis data kualitatif. Hasil penelitian menunjukkan bahwa (1) Penerapan hukum pidana materil terhadap tindak pidana peredaran narkotika yang dilakukan oleh terdakwa Siskawanti Alias Siska Binti M. Said dalam Putusan Nomor 731/Pid.Sus/2022/PN.Mks telah terbukti secara sah memenuhi unsur-unsur yang terdapat dalam Pasal 114 ayat 2 Undang-Undang RI Nomor 35 Tahun 2009 tentang Narkotika. (2) Sanksi pidana seharusnya sesuai dengan tuntutan Penuntut Umum, karena pertanggung jawaban pidana pelaku pengedar narkotika berdasarkan fakta dan keterangan dua orang saksi tersebut jelas dilakukan oleh terdakwa Siskawanti Alias Siska Binti M. Said yang merupakan seorang kurir narkotika dimana siterdakwa diperintahkan oleh Ari Sincan dengan gaji 5 (lima) juta rupiah untuk mengambil shabu kemudian diantarkan ke pembeli dengan berat berat 46,8711 gram dan berat akhir 45,3450 gram. Perbuatan terdakwa tersebut sangat merugikan dirinya sendiri dan orang lain.